“Institutions pour Bruxelles et valeurs chères à la communauté belge” par Henry Tulkens et réponse de Victor Ginsburgh - Henry Tulkens; Victor Ginsburgh (Brussels Studies, 2009)
How to find a way out of Belgium's linguistic stalemate? How to guarantee the respect of democratic principles in the use of languages?These two questions, especially crucial to Brussels and its surrounding area, are at the heart of the latest paper that Henry Tulkens, professor emeritus of political economy and public finances at UCL (Université catholique de Louvain), has published in Brussels Studies (“Double vision” collection).According to Prof. Tulkens, prospects to appease linguistic conflicts lie in determining the use of languages at the local level, abandoning the principle of jus soli and embracing the democratic and pragmatic values of bilingualism – rather than unilingualism – in the communes where a sufficient majority so wishes. This will restore a win-win situation – a positive sum game – among the communities where they would no longer be competitors, but partners with an interest in seeing the other language flourish. Brussels is cited as example, where bilingualism and firm guarantees for the Dutch-speaking minority have preserved the importance of this language, where the linguistic debate is less strident than in the city's outskirts, and where linguistic opening has been an advantage to all, as demonstrated during the recent Citizens Forum of Brussels.As with all topics in the “Double vision” collection, the text published is an invitation for a reflection and dialogue on the many sides of an issue. In this context, we also publish comments by Victor Ginsburgh, professor emeritus of political economy at ULB (Université libre de Bruxelles), in a reply to Henry Tulkens.Prof. Ginsburgh calls on the French-speakers to be realistic and grasp the national scope of the Flemish project. He rejects the idea that part of the population, at a local level, would be able to change the official language applied in the area. Instead he proposes that the minority simply learn the language of the majority, not in view of assimilation but in the interest of developing bilingualism. Lastly, he agrees with the proposal for a win-win situation: each linguistic community has much to gain when the other's culture thrives, even in “its own territory”. Nonetheless, he feels that bilingualism perhaps must make some headway before such an attitude can truly be envisaged.